At the Edges of Sleep : Moving Images and Somnolent Spectators. - Ma, Jean. (Berkeley : University of California Press, 2022)
A free open access ebook is available upon publication. Learn more at www.luminosoa.org. Many recent works of contemporary art, performance, and film turn a spotlight on sleep, wresting it from the hidden, private spaces to which it is commonly relegated. At the Edges of Sleep considers sleep in film and moving image art as both a subject matter to explore onscreen and a state to induce in the audience. Far from negating action or meaning, sleep extends into new territories as it designates ways of existing in the world, in relation to people, places, and the past. Defined positively, sleep also expands our understanding of reception beyond the binary of concentration and distraction. These possibilities converge in the work of Thai filmmaker and artist Apichatpong Weerasethakul, who has explored the subject of sleep systematically throughout his career. In examining Apichatpong's work, Jean Ma brings together an array of interlocutors--from Freud to Proust, George Méliès to Tsai Ming-liang, Weegee to Warhol--to rethink moving images through the lens of sleep. Ma exposes an affinity between cinema, spectatorship, and sleep that dates to the earliest years of filmmaking, and sheds light upon the shifting cultural valences of sleep in the present moment.
Intro -- Contents -- List of Illustrations -- Acknowledgments -- 1 Apichatpong Weerasethakul and the Turn to Sleep -- 2 Sleep Must Be Protected -- PART I: REGARDING SLEEP -- 3 Into the Dark -- 4 Exiting and Entering Early Cinema -- 5 Somnolent Journeys -- 6 Insensate Intimacies -- PART II: SLEEPING REGARD -- 7 The Regressive Thesis -- 8 Narcotic Reception -- 9 A Little History of Sleeping at the Movies -- 10 Zoning Out -- 11 Circadian Cinemas -- Notes -- Selected Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books